2021
DOI: 10.1136/bmjmilitary-2020-001754
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in barriers to mental healthcare for UK military veterans: a preliminary investigation

Abstract: IntroductionLimited UK research focuses on female military veterans’ gender-related experiences and issues when accessing civilian mental healthcare support. This study sought to illuminate a preliminary understanding of any gender differences in barriers that may discourage them accessing mental healthcare support.MethodsA total of 100 participants completed an open online survey of UK triservice veterans who identified as having experienced postmilitary mental health problems. They completed a 30-item Barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…As was identified in the current study, previous research has demonstrated that self-imposed and social stigma related to mental health treatment is common within the military population and can cause veterans to avoid seeking support (e.g., Blais & Renshaw, 2013;Mittal et al, 2013;Ouimette et al, 2011). There is a persisting association between military culture and mental health stigma (Iversen et al, 2010;Iversen et al, 2011), which may be particularly important within the female population as the stigma around female weakness may discourage helpseeking (Godier-McBard et al, 2021). Although mental health stigma is reported as one of the biggest barriers to accessing treatment for male veterans (Hoge et al, 2004), it was one of the least frequently reported themes in the current study.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…As was identified in the current study, previous research has demonstrated that self-imposed and social stigma related to mental health treatment is common within the military population and can cause veterans to avoid seeking support (e.g., Blais & Renshaw, 2013;Mittal et al, 2013;Ouimette et al, 2011). There is a persisting association between military culture and mental health stigma (Iversen et al, 2010;Iversen et al, 2011), which may be particularly important within the female population as the stigma around female weakness may discourage helpseeking (Godier-McBard et al, 2021). Although mental health stigma is reported as one of the biggest barriers to accessing treatment for male veterans (Hoge et al, 2004), it was one of the least frequently reported themes in the current study.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, female veterans have been found to experience significantly higher rates of PTSD following military service compared to male veterans (Tolin & Foa, 2008), or at least PTSD and depression rates on par with male veterans (Hoge et al, 2007). Moreover, these reports may be because experiences and difficulties of female veterans are minimised or misunderstood by health professionals (Disabled American Veterans, 2014) and often female veterans report a lack of recognition from health care professionals that they may have experienced the same trauma as male veterans, i.e., combat-related trauma (Godier-McBard et al, 2021). This inequality between the treatment of male and female veterans may be reflective of attitudes that women are secondary to men in the military due in part to the collocation policy (a policy which prohibits women from holding positions where they will be physically working in ground combat; Morris, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many military veterans make the transition from military to civilian life without difficulty; however, there remains a proportion of veterans who have experienced multiple and complex health, financial and social needs. The complex problems tend to exacerbate each other and deepen over time if appropriate support is not provided -which is in turn made more difficult by the well-documented lack of trust by veterans in the social and healthcare systems that are designed to support them [2][3][4].…”
mentioning
confidence: 99%